Factors affecting the implementation of employee whole health in the veterans health administration: a qualitative evaluation - Omonyêlé L. Adjognon; Adena Cohen-Bearak; Jenesse Kaitz; Barbara G. Bokhour; Leslie Chatelain; Martin P. Charns; David C. Mohr (BMC, 2023)
Background There is increasing recognition of the need to focus on the health and well-being of healthcare employees given high rates of burnout and turnover. Employee wellness programs are effective at addressing these issues; however, participation in these programs is often a challenge and requires large scale organizational transformation. The Veterans Health Administration (VA) has begun to roll out their own employee wellness program-Employee Whole Health (EWH)-focused on the holistic needs of all employees. This evaluation's goal was to use the Lean Enterprise Transformation (LET) model for organizational transformation to identify key factors-facilitators and barriers-affecting the implementation of VA EWH. Methods This cross-sectional qualitative evaluation based on the action research model reflects on the organizational implementation of EWH. Semi-structured 60-minute phone interviews were conducted in February-April 2021 with 27 key informants (e.g., EWH coordinator, wellness/occupational health staff) knowledgeable about EWH implementation across 10 VA medical centers. Operational partner provided a list of potential participants, eligible because of their involvement in EWH implementation at their site. The interview guide was informed by the LET model. Interviews were recorded and professionally transcribed. Constant comparative review with a combination of a priori coding based on the model and emergent thematic analysis was used to identify themes from transcripts. Matrix analysis and rapid turnaround qualitative methods were used to identify cross-site factors to EWH implementation. Results Eight common factors in the conceptual model were found to facilitate and/or hinder EWH implementation efforts: [1] EWH initiatives, [2] multilevel leadership support, [3] alignment, [4] integration, [5] employee engagement, [6] communication, [7] staffing, and [8] culture. An emergent factor was [9] the impact of the COVID-19 pandemic on EWH implementation. Conclusions As VA expands its EWH cultural transformation nationwide, evaluation findings can (a) enable existing programs to address known implementation barriers, and (b) inform new sites to capitalize on known facilitators, anticipate and address barriers, and leverage evaluation recommendations through concerted implementation at the organization, process, and employee levels to jump-start their EWH program implementation.